Could early ischemic arrhythmia triggered by purinergic activation of the transient receptor potential channels be prevented by creatine? - Vassort, Guy (Pulsus Group Inc, 2010)
Despite its degradation by ectonucleotidases, a low ATP concentration is present in the interstitial space; moreover, its level can markedly increase during various physiopathological conditions. ATP and uridine 5′-triphosphate (UTP) releases correlate with the occurrence of ventricular premature beats and ventricular tachycardia. ATP facilitates several voltage-dependent ionic currents including the L-type Ca(2+) current. More recently, ATP and UTP were also shown to induce a poor voltage-dependent, long-lasting current carried by the heterotetrameric transient receptor potential (TRP) channels TRPC3/7. ATP effects result from its binding to metabotropic P2Y2 receptors that lead to diacylglycerol formation and activation of phospholipase Cβ and inositol-1,4,5-triphosphate production. ATP also favours TRPM4 activation by increasing Ca(2+) release from the sarcoplasmic reticulum. Indeed, TRPM4 current properties match those of the Ca(2+)-activated, nonselective cationic current supporting the delayed afterdepolarizations observed under conditions of Ca(2+) overload. In the present article, it was hypothesized that creatine, at a relatively high concentration, would serve as a buffer for the sudden release of ATP and UTP during the early phase of ischemia in association with previously described arrhythmic events. The potential preventive effect of creatine was tested by analyzing its ability to antagonize the arrhythmia that occurred on inducing a coronary ligature in rats that were or were not preinjected with creatine. Electrocardiogram recordings of creatine-injected rats clearly demonstrated that both ventricular premature beats and, particularly, ventricular tachycardia markedly decreased. The effect of creatine was even more striking in early deaths. However, an injection of beta-guanidinopropionate, a creatine analogue with 1000-fold lower kinetics, had no significant protective effect.